Intrahepatic cholestasis of pregnancy and timing of delivery. (12th December 2015) - Lo, Jamie O.; Shaffer, Brian L.; Allen, Allison J.; Little, Sarah E.; Cheng, Yvonne W.; Caughey, Aaron B.
Abstract: Objective : We examined the morbidities from delivery at earlier gestational ages versus intrauterine fetal demise (IUFD) for women with intrahepatic cholestasis of pregnancy (ICP) to determine the optimal gestational age for delivery. Methods : A decision-analytic model was created to compare delivery at 35 through 38 weeks gestation for different delivery strategies: (1) empiric steroids; (2) steroids if fetal lung maturity (FLM) negative; (3) wait a week and retest if FLM negative; or (4) deliver immediately. Literature review identified 18 studies that estimated IUFD in ICP; we used the mean rate, 1.74%, and assumed a uniform distribution from 34 to 40 weeks gestation. Large cohort data was used to calculate neonatal morbidity rates at each gestational age. Maternal and neonatal quality-adjusted life years (QALYs) were combined. Univariate sensitivity and Monte Carlo analyses were performed to test for robustness. Results : Immediate delivery at 36 weeks without FLM testing and steroid administration was the optimal strategy as compared to delivery at 36 weeks with steroids (+47 QALYs) and as compared to immediate delivery at 35 weeks (+210 QALYs). Our results were robust up to a 30% increase in the rate of IUFD. Conclusion : Immediate delivery at 36 weeks in women with ICP is the optimal delivery strategy.